Viabilidade do uso de palatabilizantes em dietas para leitões de 6 a 18 kg de peso vivo - Costa, Lúcio Laudares (2001)
To determine the effect of adding flavours in simple or complex diet on the performance, blood parameters and the organs weight of pigs, a total of 192 weaning crossbred Landrace x LargeWhite pig lets weighing 6,9 kg and 23 days old were utilized, in an randomized block design experiment with factorial scheme 2x3,with two diets (simple or complex) and addition or not of two flavours (Fl e F2) in 8 replicates. It was observed that the flavour addition did not had influence (P>0,05) the weight gain, feed intake or in the feed conversion. However, the complex diet presented a better (P<0,05) feed conversion than the simple diet. The glucose concentration was influenced by the blood collection period, with higher in the pos-prandrial period.The simple diet increased more glucose in the blood in both periods. The glucose concentration was not influenced by the flavours. The insulin presented higher levels in the pos-prandial period, therefore it was also not influenced both diets types as well as the flavors tested.The weight of liver, pancreas and kidneys were not influenced by the flavours, therefore simple diet shown higher weights (P>0,05) as compared to a complex piglets diets. It was concluded that the flavours utilized did not show any effects on the pig lets performance, therefore the complex diets should be technically viable for piglets from 6 to 18 kg of live weight.